The anthropological imagination in Latin American literature - Emery, Amy Fass, 1957- (University of Missouri Press, 1996)
In this examination of the cross between anthropology and literature in contemporary Latin America, Amy Fass Emery studies how Latin American writers' experiences and studies in the field of anthropology have shaped their representations of cultural Others in fiction. She approaches her subject first in broad terms and then in close textual readings of important writers such as Alejo Carpentier, Jose Maria Arguedas, and Miguel Barnet. Emery develops the concept of an "anthropological imagination"--That is, the conjunction of anthropology and fiction in twentieth-century Latin American literature. Emery also gives consideration to documentary and testimonial writings. Analyzing fictions by authors from Cuba, Argentina, Brazil, and Peru, Emery covers a wide geographical region, as well as a diverse group of topics.